2021
DOI: 10.37741/t.69.1.10
|View full text |Cite
|
Sign up to set email alerts
|

CEE Millennial Travellers’ Attitude towards Security Measures Applied in Tourism Infrastructure

Abstract: The aim of the paper is to assess the level of Millennial travellers’ from Central and Eastern Europe safety estimated by the importance of the security measures implemented in tourism infrastructure (accommodation facilities and tourist attractions) as a way to provide a safer leisure environment. In addition, the paper examines whether tourists’ gender and economic stimulus in the form of reduced travel costs are among the factors which influence the evaluation of the significance of safety measures and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…As shown by the experience of other crises in the past (e.g., caused by terrorist attacks or natural disasters), tourists can react differently to security measures in tourism infrastructure [41], and the tourism sector is able to recover and resume its activities in the new, changed reality quite quickly, which results, among others, from the high level of competitiveness of companies operating in this market [42]. Therefore, according to Assaf and Scuderi [43], despite the difficult situation in the tourism sector, it is necessary to start working on strategies for its recovery now.…”
Section: Security Measures and The Tourism Sectormentioning
confidence: 99%
“…As shown by the experience of other crises in the past (e.g., caused by terrorist attacks or natural disasters), tourists can react differently to security measures in tourism infrastructure [41], and the tourism sector is able to recover and resume its activities in the new, changed reality quite quickly, which results, among others, from the high level of competitiveness of companies operating in this market [42]. Therefore, according to Assaf and Scuderi [43], despite the difficult situation in the tourism sector, it is necessary to start working on strategies for its recovery now.…”
Section: Security Measures and The Tourism Sectormentioning
confidence: 99%
“…Students and their preferences, goals, and motives are of interest to researchers but unfortunately only piecemeal in the area of sustainable tourism topics. The findings of Eusébio and Carneiro [66][67][68] have shown that we are dealing with certain groups of young tourists. For some, economic motives are more important, and for others, cultural and natural resources and entertainment offers or products based on sustainability are more important.…”
Section: Gen Z Travellers and Their Attitude To The Riskmentioning
confidence: 94%
“…Reviews left exclusively by millennial guests, both foreign and Peruvian were analyzed. Several authors mention the scarce research regarding tourism focused on the millennial segment despite the fact that they play a relevant role for tourism businesses [17], [28], [29]. The IDN Research Institute categorizes Indonesia's millennial population into two categories, Senior Millennials; those born from 1984-1991 (currently 31 to 38 years old) and Junior Millennials; those born from 1992-1999 (currently 23 to 30 years old) [30].…”
Section: Methodsmentioning
confidence: 99%